2019
DOI: 10.4049/jimmunol.1801384
|View full text |Cite
|
Sign up to set email alerts
|

Tetraspanin CD82 Organizes Dectin-1 into Signaling Domains to Mediate Cellular Responses to Candida albicans

Abstract: Tetraspanins are a family of proteins possessing four transmembrane domains that help in lateral organization of plasma membrane proteins. These proteins interact with each other as well as other receptors and signaling proteins, resulting in functional complexes called "tetraspanin microdomains." Tetraspanins, including CD82, play an essential role in the pathogenesis of fungal infections. Dectin-1, a receptor for the fungal cell wall carbohydrate b-1,3-glucan, is vital to host defense against fungal infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 62 publications
(78 reference statements)
0
33
0
Order By: Relevance
“…response (54)(55)(56). We recently reported that CD82 mediates dectin-1 clustering and enables robust downstream signaling (34). The tetraspanin CD37 interacts with dectin-1 to regulate surface expression in immune cells (48).…”
Section: Discussionmentioning
confidence: 99%
“…response (54)(55)(56). We recently reported that CD82 mediates dectin-1 clustering and enables robust downstream signaling (34). The tetraspanin CD37 interacts with dectin-1 to regulate surface expression in immune cells (48).…”
Section: Discussionmentioning
confidence: 99%
“…Next, we examined whether the defects in ROS affected the fungal killing ability by Skap2-/- DIV neutrophils. DIV neutrophils were incubated with C. glabrata for 24 hours, or C. albicans for 2 hours, and then fungal survival was measured using the PrestoBlue viability dye conversion (Xu et al, 2018, Tam et al, 2019). Compared to WT, Skap2-/- DIV neutrophils demonstrated significantly decreased fungicidal activity after infection with C. glabrata (Figure 5D-E) while infection with C. albicans typically also led to a decrease in fungal killing in 4 out of 5 experiments (Figure 5D, F).…”
Section: Resultsmentioning
confidence: 99%
“…The PrestoBlue assay kit (Thermo Fisher) was used to measure fungal viability following co-culture with WT and Skap2-/- DIV neutrophils (Tam et al, 2019, Xu et al, 2018, Negoro et al, 2020). DIV neutrophils in cRPMI were plated in triplicate 96-well non-tissue culture treated plates at a density of 1 × 10 5 cells/well.…”
Section: Methodsmentioning
confidence: 99%
“…Recent reports have detailed a mechanism whereby decreased Dectin-1 signaling confers risk of candidemia. CD82 is involved in the clustering of Dectin-1 receptors, and the efficient activation of intracellular signaling upon ligand binding (Tam et al, 2019). Variants in CD82 are associated with both candidemia risk and decreased cytokine production upon stimulation with fungal ligands (Tam et al, 2019).…”
Section: Opportunistic Mucosal Infections Bymentioning
confidence: 99%
“…CD82 is involved in the clustering of Dectin-1 receptors, and the efficient activation of intracellular signaling upon ligand binding (Tam et al, 2019). Variants in CD82 are associated with both candidemia risk and decreased cytokine production upon stimulation with fungal ligands (Tam et al, 2019). It is less clear if there is a role for variants in CLEC7A, the gene encoding Dectin-1.…”
Section: Opportunistic Mucosal Infections Bymentioning
confidence: 99%